Community home elderly care services, multidimensional health and social participation of chronically ill elderly—Empirical analysis based on propensity score matching and multiple mediation analysis - Jiang, He; Liu, Zixuan (Frontiers in Public Health, 2023)
Introduction In recent years, China's aging process has deepened rapidly, the disease spectrum of the population has undergone major changes, the proportion and scale of elderly patients with chronic diseases are growing rapidly, and the multidimensional health problems of the chronically ill elderly are prominent, seriously affecting the participation of the chronically ill elderly in family, community, and social development. In response, China has implemented the “active response to population aging strategy,” accelerated the development of community home elderly care services, and encouraged the chronically ill elderly to continue to play a role through social participation. So how does the community-based home-based medical care service affect the social participation of the chronically ill elderly? Is an important subject. Methods Based on the 2018 China Longitudinal Aging Social Survey and the propensity score matching method to measure the impact of community home elderly care services on the four types of social participation of chronically ill elderly, including economic participation, family participation, voluntary participation, and political participation, and group differences, and uses the multiple mediation analysis method to explore the mechanism and effect of community home elderly care services on the four types of social participation of chronically ill elderly. Results (1) Community home elderly care services have an asymmetric impact on the social participation of the chronically ill elderly, and have generally promoted the level of social participation of the chronically ill elderly. (2) Community home elderly care services change the social participation arrangements of the chronically ill elderly by driving and inhibiting effects, so that it has a tendency to reduce economic participation and increase voluntary participation and political participation as a whole. This feature shows group differences among the chronically ill elderly of different ages, education levels, living arrangements and community types. (3) Community home elderly care services have an asymmetric impact on various social participation of the chronically ill elderly through the multidimensional health mediation mechanism. Conclusion (1) With the continuous deepening of the interweaving between the growth of chronic diseases and the aging of the population in China, the development of a positive aging society must attach great importance to the important role of social participation for the chronically ill elderly. (2) Strengthen the development of physical, psychological, and social adaptation and other health abilities of the chronically ill elderly, shape their awareness of social participation, and give the chronically ill elderly a reasonable social role orientation. (3) Through policy incentives, promote the realization of fairness, justice, adequacy, and sustainability of community home elderly care services. (4) Pay special attention to the penetration, integration, and application of digital technology into the field of community home elderly care services to effectively protect the health of chronically ill elderly, ensure that the elderly with different chronic diseases participate in social activities of high quality, enjoy a high-quality happy life, and promote the high-quality development of the aging society.